Optimizing sustainable agricultural production under uncertainty: a multi-objective model for crop selection and land allocation - Musawer Zeb; Waqas Ahmed; Muhammad Moazzam; Salman Sagheer Warsi; Muhammad Salman Habib (Environment, Development and Sustainability, 2026)

Global manta and devil ray population declines: Closing policy and management gaps to reduce fisheries mortality - Betty J.L. Laglbauer; Nidhi G. D'Costa; Joshua D. Stewart; Marta D. Palacios; Melissa Cronin; Daniel Fernando; Nerea Lezama-Ochoa; Asia O. Armstrong; Rima W. Jabado; Sarah Fowler; Julia M. Lawson; Olga Koubrak; et al. (Biological Conservation, 2026)

A functional self-assembled layer with preferential sodium adsorption sites for ultra-stable sodium metal batteries - Moazzam Ali; Asif Mahmood; Muhammad Ali; Samia Aman; Hamid Hussain; Xuan Zhang; Yinzhu Jiang; Xufeng Lin; Muhammad Yousaf (Chemical Engineering Journal, 2025)

Influence of Aloe Vera Gel and Neem Extract Application on Postharvest Quality and Shelf Life of Prunus persica - Muhammad Talha; Moazzam Anees; Mubeen Sarwar; M. Rizwan Tariq; Zain Mushtaq; Abdulrahman Alasmari; Anum Nazir; Nazir Ahmad (Applied Fruit Science, 2025)

Dynamics of land cover/land use with heat islands phenomenon and its ecological evaluation using remote sensing data (1992–2022) - Noreena; Muhammad Farhan Ul Moazzam; Muhammad Jamil; Sana Arshad (Environment, Development and Sustainability, 2025)

Precision in Rice Variety Classification using Stacking-based Ensemble Learning - Md. Masudul Islam; Galib Muhammad Shahriar Himel; Golam Moazzam; Mohammad Shorif Uddin (Journal of Cereal Science, 2025)

Elevation-dependent snow cover dynamics and associated topo-climate impacts in upper Indus River basin - Muhammad Farhan Ul Moazzam; Abhishek Banerjee; Ghani Rahman; Byung Gul Lee (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Nanoarchitectonics of molybdenum rich crown shaped polyoxometalates based ionic liquids reinforced on magnetic nanoparticles for the removal of microplastics and heavy metals from water - Hameed Ullah; Taghrid S. Alomar; Muhammad Tariq; Najla AlMasoud; Moazzam H. Bhatti; Muhammad Ajmal; Zahra Nazar; Muhammad Nadeem; Hafiz Muhammad Asif; Muhammad Sohail (Journal of Environmental Chemical Engineering, 2024)

Cities in the heat: Unveiling the urbanized impacted surface urban heat island of South Korea's metropolises - Muhammad Farhan Ul Moazzam; Sanghyun Kim; Byung Gul Lee (Remote Sensing Applications: Society and Environment, 2024)

Climate dynamics and the effect of topography on snow cover variation in the Indus-Ganges-Brahmaputra river basins - Abhishek Banerjee; Shichang Kang; Muhammad Farhan Ul Moazzam; Michael E. Meadows (Atmospheric Research, 2024)

Eco-toxicological impacts of industrial wastewater and the role of bio-electrochemical systems (BES) in remediation: a review - Muhammad Usman; Zhenhua Zhao; Olive Mekontchou Yemele; Muhammad Ibrahim; Waleed Raza; Zia Ur Rehman; Abduelrahman Adam Omer; Mir Moazzam Ali Talpur; Mouna Jeridi; Ghulam Abbas Ashraf; Hafsat Alhassan Danjaji (Clean Technologies and Environmental Policy, 2024)

Unraveling the role of natural functional oils in modulating osteoarthritis related complications - Muhammad Asim Shabbir; Fakiha Mehak; Moazzam Rafiq Khan; Waqar Ahmed; Muhammad Furqan Nawaz; Abdo Hassoun; Zuhaib F. Bhat; Rana Muhammad Aadil (Critical Reviews in Food Science and Nutrition, 2024)

Elevation dependent climate assessment and its influence on snow cover variability in Hindu Kush Himalayan region using Google Earth Engine for the period of 2003–2021 - Muhammad Farhan Ul Moazzam; Abhishek Banerjee; Ghani Rahman; Byung Gul Lee (Remote Sensing Applications: Society and Environment, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Evaluating the relative influence of climate and human activities on recent vegetation dynamics in West Bengal, India - Abhishek Banerjee; Shichang Kang; Michael E. Meadows; Wasim Sajjad; Ali Bahadur; Muhammad Farhan Ul Moazzam; Zilong Xia; Joseph Mango; Bappa Das; Kelly L. Kirsten (Environmental Research, 2024)

Utilizing machine learning and CMIP6 projections for short-term agricultural drought monitoring in central Europe (1900–2100) - Safwan Mohammed; Sana Arshad; Firas Alsilibe; Muhammad Farhan Ul Moazzam; Bashar Bashir; Foyez Ahmed Prodhan; Abdullah Alsalman; Attila Vad; Tamás Ratonyi; Endre Harsányi (Journal of Hydrology, 2024)

Urbanization influenced SUHI Of 41 megacities of the world using big geospatial data assisted with google earth engine - Muhammad Farhan Ul Moazzam; Byung Gul Lee (Sustainable Cities and Society, 2024)

Unravelling the elevation-dependent warming in the Indus Basin - Muhammad Farhan Ul Moazzam; Sudeep Thakuri; Ghani Rahman; Byung Gul Lee (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Corrigendum to “Priming of adipose-derived stem cells with curcumin prior to cryopreservation preserves their functional potency: Towards an ‘Off-the-shelf’ therapy for burns” [Cryobiology 110 (2023) 69–78] - Maryam Azam; Hafiz Ghufran; Saba Tasneem; Azra Mehmood; Kausar Malik; Muhammad Amin Yousaf; Moazzam N. Tarar; Shehla Javed Akram; Sheikh Riazuddin (Cryobiology, 2023)

Spatio-temporal snow cover change in the early twenty-first century using improved MODIS dataset: a case study of District Hunza, Pakistan - Muhammad Farhan Ul Moazzam; Ghani Rahman; Kokab Saba Ali; Byung Gul Lee (Climate Dynamics, 2023)

Priming of adipose-derived stem cells with curcumin prior to cryopreservation preserves their functional potency: Towards an ‘Off-the-shelf’ therapy for burns - Maryam Azam; Hafiz Ghufran; Saba Tasneem; Azra Mehmood; Kausar Malik; Muhammad Amin Yousaf; Moazzam N. Tarar; Shehla Javed Akram; Sheikh Riazuddin (Cryobiology, 2023)

Evaluating dual exposure by using climate-conflict vulnerability index on the coastal districts of Sindh, Pakistan - Noor Fatima; Aamir Alamgir; Moazzam Ali Khan; Muhammad Owais (Environmental Monitoring and Assessment, 2022)

First Records of Xanthochromism in Four Marine Fish Species Collected from the Arabian Sea Coasts of Pakistan - Laith A. Jawad; Muhammad Moazzam; Hamid Badar Osmany; Abdul Rahim (Thalassas: An International Journal of Marine Sciences, 2021)

Extent and pattern of damage in wheat caused by three different species of storage insect pests - Muhammad Waqar Hassan; Ghulam Sarwar; Muhammad Aslam Farooqi; Moazzam Jamil (International Journal of Tropical Insect Science, 2021)

Phylogenomics and species delimitation for effective conservation of manta and devil rays - Jane Hosegood; Emily Humble; Rob Ogden; Mark de Bruyn; Simon Creer; Guy M. W. Stevens; Mohammed Abudaya; Kim Bassos‐Hull; Ramon Bonfil; Daniel Fernando; Andrew D. Foote; Helen Hipperson; et al. (Molecular Ecology, 2020)
Practical biodiversity conservation relies on delineation of biologically meaningful units. Manta and devil rays (Mobulidae) are threatened worldwide, yet morphological similarities and a succession of recent taxonomic changes impede the development of an effective conservation strategy. Here, we generate genome‐wide single nucleotide polymorphism (SNP) data from a geographically and taxonomically representative set of manta and devil ray samples to reconstruct phylogenetic relationships and evaluate species boundaries under the general lineage concept. We show that nominal species units supported by alternative data sources constitute independently evolving lineages, and find robust evidence for a putative new species of manta ray in the Gulf of Mexico. Additionally, we uncover substantial incomplete lineage sorting indicating that rapid speciation together with standing variation in ancestral populations has driven phylogenetic uncertainty within Mobulidae. Finally, we detect cryptic diversity in geographically distinct populations, demonstrating that management below the species level may be warranted in certain species. Overall, our study provides a framework for molecular genetic species delimitation that is relevant to wide‐ranging taxa of conservation concern, and highlights the potential for genomic data to support effective management, conservation and law enforcement strategies.

Integrated Application of Organic Amendments with Alcaligenes sp. AZ9 Improves Nutrient Uptake and Yield of Maize (Zea mays) - Azhar Hussain; Maqshoof Ahmad; Muhammad Zahid Mumtaz; Sajjad Ali; Rubab Sarfraz; Muhammad Naveed; Moazzam Jamil; Christos A. Damalas (Journal of Plant Growth Regulation, 2020)

Synthesis of new chiral 1,3,4-thiadiazole-based di- and tri-arylsulfonamide residues and evaluation of in vitro anti-HIV activity and cytotoxicity - Maria Shafique; Shahid Hameed; Muhammad Moazzam Naseer; Najim Aboud Al-Masoudi (Molecular Diversity, 2018)

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; Peter M. Kyne; Riley A. Pollom; David A. Ebert; Colin A. Simpfendorfer; Gina M. Ralph; Shaikha S. Al Dhaheri; K. V. Akhilesh; Khadeeja Ali; Mohamud Hassan Ali; Tariq M. S. Al Mamari; K. K. Bineesh; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.

In vitro preconditioning of insulin-producing cells with growth factors improves their survival and ability to release insulin - Muhammad Sohail Anjum; Azra Mehmood; Faiza Mahmood; Muhammad Ali; Moazzam Nazir Tarrar; Shaheen N. Khan; Sheikh Riazuddin (Journal of Biosciences, 2018)

Effect of biochar and quicklime on growth of wheat and physicochemical properties of Ultisols - Zaffar Malik; Zong Yutong; Lu ShengGao; Ghulam Hassan Abassi; Shafaqat Ali; Muhammad Imran khan; Muhammad Kamran; Moazzam Jamil; Mohammad I. Al-Wabel; Muhammad Rizwan (Arabian Journal of Geosciences, 2018)

Comparison of rhizosphere properties as affected by different Bt- and non-Bt-cotton (Gossypium hirsutum L.) genotypes and fertilization - Maqshoof Ahamd; Waleed Mumtaz Abbasi; Moazzam Jamil; Muhammad Iqbal; Azhar Hussain; Muhammad Fakhar-u-Zaman Akhtar; Farheen Nazli (Environmental Monitoring and Assessment, 2017)

Diazoxide preconditioning of endothelial progenitor cells from streptozotocin-induced type 1 diabetic rats improves their ability to repair diabetic cardiomyopathy - Muhammad Ali; Azra Mehmood; Muhammad Sohail Anjum; Moazzam Nazir Tarrar; Shaheen N. Khan; Sheikh Riazuddin (Molecular and Cellular Biochemistry, 2015)

Effect of Thermal Treatment on Meat Proteins with Special Reference to Heterocyclic Aromatic Amines (HAAs) - Muhammad Asim Shabbir; Ali Raza; Faqir Muhammad Anjum; Moazzam Rafiq Khan; Hafiz Ansar Rasul Suleria (Critical Reviews in Food Science and Nutrition, 2015)

POM analyses of anti-kinase activity of thirteen peptide alkaloids extracted from Zizyphus species - Moulay H. Youssoufi; Taibi Ben Hadda; Ismail Warad; Muhammad Moazzam Naseer; Yahia Nasser Mabkhot; Ammar Bader (Medicinal Chemistry Research, 2015)

Synthesis and effect of substituent position on anti-inflammatory activity of 3-(halobenzyl)isocarbostyrils - Tariq Mahmood Babar; Muhammad Moazzam Naseer; Farukh Iftakhar Ali; Nasim Hasan Rama; Taibi Ben Hadda (Medicinal Chemistry Research, 2014)

POM analyses of antimicrobial activity of some 2,3-armed 4,5,6,7-tetrahydro-1-benzothiophenes: favourable and unfavourable physico-chemical parameters in design of antibacterial and mycolytic agents - Taibi Ben Hadda; Sajal Srivastava; Barnali Das; Héctor Salgado-Zamora; Usama Shaheen; Ammar Bader; Muhammad Moazzam Naseer (Medicinal Chemistry Research, 2014)